A collage of cholesterol interaction motifs in the serotonin1A receptor: An evolutionary implication for differential cholesterol interaction. (July 2019) - Fatakia, Sarosh N.; Sarkar, Parijat; Chattopadhyay, Amitabha
Graphical abstract: Highlights: The amino acid sequence of serotonin1A receptor TM V is largely conserved among vertebrate species. TM V and ICL3 fragment contain a conserved collage of putative cholesterol interaction motifs. The serotonin1A receptor can interact with membrane cholesterol in twenty possible ways. The collage of cholesterol interaction sites are relevant in membranes of varying cholesterol content. Abstract: The serotonin1A receptor is a representative member of the G protein-coupled receptor (GPCR) superfamily and acts as an important drug target. In our previous work, we comprehensively demonstrated that membrane cholesterol is necessary in the organization, dynamics and function of the serotonin1A receptor. In this context, analysis of high-resolution GPCR crystal structures in general and in silico studies of the serotonin1A receptor in particular, have suggested the presence of cholesterol interaction sites (hotspots) in various regions of the receptor. In this work, we have identified an evolutionarily conserved collage of four categories of cholesterol interaction motifs associated with transmembrane helix V and the adjacent intracellular loop 3 fragment of the vertebrate serotonin1A receptor. This collage of motifs represents a total of twenty diverse context-dependent cholesterol interaction configurations. We envision that the gamut of cholesterol interaction sites, characterized by sequence plasticity in cholesterol interaction, could be relevant in receptor-cholesterol interaction in membranes of varying cholesterol content and organization, as found in diverse cell types. We conclude that an evolutionarily conserved mechanism of GPCR-cholesterol interaction allows the serotonin1A receptor to adapt to diverse membrane cholesterol levels during natural evolution.